The development of critical thinking skills through the evaluation of internet materials - Barnett, David (My University, 2017)
The internet supplies a continuous stream of information to our students. The information gleaned from the internet is ever-changing and scanty and researchers have used the term “paucity” to describe internet information. It is difficult to trust this information and value it as knowledge. The need for developing Critical Thinking and its application is advanced both internationally and in South Africa .This study, investigated the development of specific critical thinking skills for the purpose of evaluating internet materials for trustworthiness. Within this study a series of lessons were designed to develop Critical Thinking skills amongst a group of Grade 11 students at a private high school in South Africa. Once these skills were acquired the students were able to make a comparison between different internet materials and they made a well-reasoned argument about the credibility of these materials. The key skills were taught through the use of a Learning Management System (LMS). The LMS was used as a medium for isolating selected internet materials and to develop a pathway of learning. Several educational theories, models and philosophies were investigated as they were layered into the fabric of this research report. Critical thinking skills were developed through a blended approach. Although a LMS was used as a primary medium of the Critical Thinking process the teacher was the key agent for its facilitation. The research premise was based on deductive reasoning and presumed that it was necessary to use Critical Thinking to search internet material for trustworthiness. The design made use of a case study as the preferred method to investigate the premise. An inductive approach was then implemented to interpret the data obtained from the evaluation of internet materials. Pre and post tests and scales were instituted and a comparison was made of the students’ confidence and ability to evaluate internet materials using specific critical thinking skills. When comparisons were made of both qualitative and quantitative results there was evidence that there was an enhancement and effective application of the specific critical thinking skills brought about through this intervention.
Submitted in partial fulfilment of the requirements for the degree Masters in Education (Educational Technology) School of Education, Faculty of Humanities, University of the Witwatersrand, 2016
Keywords: Internet in education--South Africa; Education--South Africa--Computer network resources; Educational technology--South Africa